2018
DOI: 10.1016/j.artd.2018.07.002
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of depression and prior opioid use on pain and opioid requirements after total joint arthroplasty

Abstract: BackgroundPreoperative opioid use causes increased pain and opioid requirements after total joint arthroplasty (TJA), but the effect of depression on this relationship is not well defined.MethodsWe conducted a retrospective review of primary TJA patients using an institutional database. Demographic variables, inpatient opioid requirements, and discharge prescription quantities were collected and compared between patients with and without a prior diagnosis of depression in both the prior opioid-using and nonusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 35 publications
2
4
0
Order By: Relevance
“…Although it is important to be aware of the association between diabetes mellitus and smoking and increased postoperative opioid use, these are largely nonmodifiable risk factors at the time of treatment for acute injuries. In agreement with prior studies, we did not find a significant association between depression, fracture type, or fixation method and postoperative opioid prescription (Rubenstein, Grace, Croci, & Ward, 2018; Strike, Sieber, Gottschalk, & Mears, 2013).…”
Section: Discussionsupporting
confidence: 92%
“…Although it is important to be aware of the association between diabetes mellitus and smoking and increased postoperative opioid use, these are largely nonmodifiable risk factors at the time of treatment for acute injuries. In agreement with prior studies, we did not find a significant association between depression, fracture type, or fixation method and postoperative opioid prescription (Rubenstein, Grace, Croci, & Ward, 2018; Strike, Sieber, Gottschalk, & Mears, 2013).…”
Section: Discussionsupporting
confidence: 92%
“…Surgical patients with OUD have distinct characteristics and require clinical care that is responsive to their unique needs, including pain and withdrawal management. 9 , 10 Consistent with other literature, we found that surgical patients with OUD were disproportionally insured by Medicaid 4 , 42 and younger, 4 more frequently experienced mental health comorbidities, 43 , 44 and more often had a patient-directed discharge. 45 Our finding that 1.3% of surgical patients had OUD is higher than another population-based study that found 0.6% prevalence, 5 but that study used International Classification of Diseases, Ninth Revision codes that are known to be less sensitive for identifying OUD than the ICD-10 codes that we used.…”
Section: Discussionsupporting
confidence: 89%
“…[43][44][45] As seen in our study cohort, patients with anxiety and/or depression are also more likely to be taking opioid medication prior to surgery. 13,48 As opioid consumption is associated with undesirable outcomes post-surgery, 15 strategies aimed at reducing opioid consumption pre-surgery may also be relevant.…”
mentioning
confidence: 99%